Randomized clinical trial on indirect resin composite and ceramic laminate veneers: Up to 10-year findings. (July 2019) - Gresnigt, M.M.M.; Cune, M.S.; Jansen, K.; van der Made, S.A.M.; Özcan, M.
Abstract: Objectives: In this randomized split-mouth clinical trial the survival rate and quality of survival of indirect resin composite and ceramic laminate veneers were evaluated. Methods: A total of 48 indirect resin composite (Estenia; n = 24) and ceramic laminate veneers (IPS Empress Esthetic; n = 24) were placed on maxillary anterior teeth. Veneer preparations with incisal overlap were performed using a mock up technique. Survival of the restoration was considered the primary outcome measure and reported using Kaplan-Meier statistics and survival curves compared by means of Log Rank (Mantel-Cox) test. After luting, restorations were evaluated by calibrated operators at baseline and every year thereafter, using modified USPHS criteria and compared by means of Mann-Whitney U test. Results: In total, 6 failures were observed, consisting of debonding (n = 3) and fracture (n = 3), all in the group of the indirect resin composite laminate veneers. Cumulative chance on survival after 10 years of the indirect resin composite and ceramic veneers was 75% (se 3, 8%) and 100% respectively (p = 0.013). Of the surviving 42 laminate veneers, the variables 'color match' (p = 0.002), 'surface roughness' (p = 0.000), 'fracture of the restoration' (p = 0.028), and 'wear of the restoration' (p = 0.014), were significantly less favourable among the composite laminate veneers as well. Conclusions: The ceramic veneers on maxillary anterior teeth in this study performed significantly better compared to the composite indirect laminate veneers after a decade, both in terms of survival rate and in terms of quality of the surviving restorations. Clinical Relevance: When indicated, anterior ceramic laminate veneers may be preferred over indirect composite laminate veneers.